Numerical study of a hybrid photovoltaic/thermal PVT solar collector using three different fluids - Ghellab, A; Boukelia, T; .Djimli, TE.Djimli; . Kaabi, S; . Kaabi, . Kaabi,A A (جامعة الوادي - university of el oued, 2021)
Hybrid photovoltaic and thermal (PV/T) systems have been widely used for the combination of PV modules and solar thermal collectors to generate both electrical energy and heat at the same time. In the present work, a numerical model has been developed to simulate the performances of a hybrid photovoltaic/thermal (PV/T) solar collector. Furthermore, a comparative study has been performed between the hybrid PV/T working with three conventional working fluids; air, water, and specified nanofluid (AL2O3+ water). The obtained results show that the use of the Alumina nanofluid is the best choice to increase the heat removal, and to improve the performances of the collector with the values of 73.28%, 10.37% and 99.21% for the thermal, electrical and global efficiency respectively. On the other hand, the PVT collector working with air as the primary fluid is the worst in terms of electrical, thermal, and global performances with the lowest values of 9.506 %, 41.55%, and 65.315% respectively.
Article
Keywords: Hybrid solar collector, Nanofluid, Numerical study, Performance, Nanofluid